Bortezomib‐based therapy combined with high cut‐off hemodialysis is highly effective in newly diagnosed multiple myeloma patients with severe renal impairment. Issue 7 (July 2015) - Zannetti, Beatrice Anna; Zamagni, Elena; Santostefano, Marisa; De Sanctis, Lucia Barbara; Tacchetti, Paola; Mancini, Elena; Pantani, Lucia; Brioli, Annamaria; Rizzo, Raffaella; Mancuso, Katia; Rocchi, Serena; Pezzi, Annalisa; et al.
<x xml:space="preserve">Abstract</x> Multiple myeloma (MM) is often associated with renal insufficiency (RI) which adversely influences the prognosis. Several studies demonstrated that bortezomib can improve both renal function and outcome. We prospectively evaluated 21 newly diagnosed MM patients with severe renal impairment secondary to tubular‐interstitial damage, most of them due to myeloma kidney, who were primarily treated with bortezomib‐based therapy combined with high cut‐off hemodialysis (HCOD). The median serum creatinine level at baseline was 6.44 mg dL−1 and calculated median estimated glomerular filtration rate (eGFR), according to Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) creatinine equation, was 8 mL/min/1.73 m2. Serum free light chain (sFLC) median concentration was 6, 040 mg L−1. Post induction and best stringent complete response rates were 19 and 38%, respectively. Responses were fast, occurring within a median of 1.4 months. The combination of bortezomib and HCOD led to a prompt and remarkable (>90%) decrease in sFLC levels. Sixteen patients (76%) became dialysis independent within a median of 32 days. With a median follow up of 17.2 months, the 3‐year PFS and OS were 76 and 67%, respectively. No early deaths were observed. This study demonstrates that incorporation of bortezomib into induction therapy combined with HCOD is a highly effective strategy in rescuing renal function and improving outcomes in patients with MM and RI. Am. J. Hematol. 90:647–652, 2015. © 2015 Wiley Periodicals, Inc.